Rancang Bangun Kendali Sekuen untuk Sambungan Jala-Jala Listrik Menggunakan Cycloconverter - Erdani, Yuliardi; Setiawan, Aris Eko; Pratama, Maulana Aria (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2010)
This developed cycloconverter circuit simulates grid connector circuit using two function generators, which substitute AC power. The first function generator was used to represent input wave from PLN with 50 Hz frequency. The other function generator was used to represent input wave from new generator with 10-90 Hz frequency. Such initial condition enabled us to control the frequency increase from 10Hz – 40Hz to 50Hz and decrease from 60Hz – 90Hz to 50Hz. This cycloconverter used trigger circuit to activate its electrical components. The trigger circuit contains trigger parts such as thyristor and MOSFET. All hardware components in this circuit were controlled by microcontroller ATMega 8535. This controller manages all trigger circuits that were needed by cycloconverter. The experiment result shows that the cycloconverter wasable to modify frequency and phase angle, so that it enabled the connection to the electrical grid.